Body-fitting customisation of motorcycle seats: an investigation of consumer requirements. (18th February 2008) - Ong, Min Huey; Wagner, Helen; Tuck, Christopher; Hague, Richard
This paper discusses the results of an investigation into the customisation of motorcycle seats. Results showed that the majority of motorcyclists felt discomfort during long distance travelling and that a customised motorcycle seat that exactly fits to the body geometry appeals to the majority of motorcyclists surveyed. Motorcyclists are willing to pay a premium for the customised seat and even wait a longer time for the customised product. The important factors motorcyclists considered when acquiring customised seats include effectiveness, quality/reliability, wellbeing and injury prevention. Although there are some motorcyclists who prefer aesthetic customisation, most motorcyclists value functionality and wellbeing above all these. Additionally, not only do the motorcyclists want customised seats for their bike, they are interested in having other parts of the motorcycle customised too.